Labour productivity and its assessment - Носова, О. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
Labour market is one of the most important factors of economic growth, which is mainly determined by labour productivity. Disparity between wage and growth of labour productivity prevents the economies of the Eastern European countries from growing. Despite the radical economic reforms in Eastern Europe, one can still observe high unemployment rate, low labour productivity, deterioration in the quality of labour. New institutions in the labour market are designed to strengthen and adopt formal institutions, promote stable demand for labour and income policy. The article focuses on a critical analysis of theoretical approaches to labour productivity and empirical assessment of productive efficiency in Kharkiv region.State policy on supporting training and education affects the future opportunities for individuals and the ability of firms to enter new markets and adopt new technologies. It is also supposed to facilitate the allocation of labour by its productivity rate as well as help employees to cope with mobility.Improving the regional investment attractiveness goes hand in hand with enhancing human capital. A skilled workforce is essential for firms to adopt new and more productive technologies, and a better investment climate enhances the returns of investment in education. As firms are offered more opportunities and better access to new technologies, the demand for more skilled workers increases and the firms have stronger incentives to get engaged in growth-enhancing activities, which raise both individual and social returns to education.From the investment climate perspective, the main issues are how labour market interventions influence the opportunities and incentives for firms to invest in a productive way, to create jobs and expand operations. Regulations might reduce incentives for attracting new investments, adjusting the organization of work, taking advantage of new technologies, or hiring more employees.